SEJARAH PERGERAKAN PARTAI MASYUMI DI INDONESIA TAHUN 1943-1960 - Mariaty, Utari; Melay, Ridwan; Saiman, Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: In the history of the process of political development in Indonesia, some of the political parties involved in the process of identity affirmation of Islam in Indonesian politics. One of the political party whose role is Masjumi. Masjumi trip since it was established on 7 November 1945 and disbanded in 1960 full of dynamics, both within the internal Masjumi or when dealing with the government and President Soekarno. This research have a purpose to know about (1) the early history of the founding of the Masjumi (2) political conditions in Indonesia before standing Masjumi (3) Masjumi role in government (4) because the dissolution Masjumi. This research use a qualitative method with approach history and techniques of data collection in the form of literature and documentation. The results of this research indicate that during its existence in Indonesia, Masjumi is a party that was involved in the administration. Masjumi relationship with President Sukarno had experienced a harmonious relationship, especially during the revolution. That relationship has shifted lead to conflicts, especially since the desire of the President to bury the political parties. Masjumi party leader's decision to break up, to be accepted by members of the Masjumi with no resistance to the leadership Masjumi.Keywords: Masjumi Party, The Presidential Decree of August 17, 1960